An Efficient Method for Approximately Simulating Drainage Capability for Urban Flood - Li, Donglai; Hou, Jingming; Xia, Junqiang; Tong, Yu; Yang, Dong; Zhang, Dawei; Gao, Xujun (Frontiers in Earth Science, 2020)
Assessing the performance and capability of drainage-pipes is significance for computing urban flood. However, the availability of drainage-pipe data is not available in many urban areas and therefore raising the problem for computing the drainage capability in an approximate way. To resolve this problem, a kind of new approach improved from the existing approach, termed as Inlet-drainage approach is proposed by assuming the drainage effects as subtracted mass in the particular parts, e.g. the area with gullies or inlets. The proposed approach is incorporated into a 2D hydrodynamic model for surface flow to simulate the coupled rainfall-runoff-drainage-inundation processes. Through validated against the measurement and modeled results in two test cases involving the ideal and realistic urban catchment, it is demonstrated that the proposed new approach could provide fairly good modeled results for computing drainage effects. More importantly, the new approach is simple and easy to implement.